Preparing to manage coral reefs for ocean acidification: lessons from coral bleaching. Issue 1 (17th December 2012) - Mcleod, Elizabeth; Anthony, Kenneth RN; Andersson, Andreas; Beeden, Roger; Golbuu, Yimnang; Kleypas, Joanie; Kroeker, Kristy; Manzello, Derek; Salm, Rod V; Schuttenberg, Heidi; Smith, Jennifer E
Abstract : Ocean acidification is a direct consequence of increasing atmospheric carbon dioxide concentrations and is expected to compromise the structure and function of coral reefs within this century. Research into the effects of ocean acidification on coral reefs has focused primarily on measuring and predicting changes in seawater carbon (C) chemistry and the biological and geochemical responses of reef organisms to such changes. To date, few ocean acidification studies have been designed to address conservation planning and management priorities. Here, we discuss how existing marine protected area design principles developed to address coral bleaching may be modified to address ocean acidification. We also identify five research priorities needed to incorporate ocean acidification into conservation planning and management: (1) establishing an ocean C chemistry baseline, (2) establishing ecological baselines, (3) determining species/habitat/community sensitivity to ocean acidification, (4) projecting changes in seawater carbonate chemistry, and (5) identifying potentially synergistic effects of multiple stressors.